Lethal and sublethal effects of synthetic and bioinsecticides toward the invasive ambrosia beetle Xylosandrus compactus. Issue 5 (5th February 2023) - Gugliuzzo, Antonio; Giuliano, Gaetano; Rizzo, Roberto; Tropea Garzia, Giovanna; Biondi, Antonio
Abstract: BACKGROUND: Exotic ambrosia beetles are emerging widespread pests of several wild and managed trees and shrubs. Xylosandrus compactus (Eichhoff) is one of the most invasive species causing damage to a broad range of host plants. Little information is available on its control, including the impact of insecticides. Bioassays were conducted to evaluate the potential of four bioinsecticides and seven synthetic insecticides in controlling X. compactus . Beetle mortality and sublethal effects on tunneling, cultivation of the mutualist fungus and reproduction were assessed. RESULTS: Concentration–mortality curves were determined for all tested insecticides. Lambda‐cyhalothrin was the most toxic insecticide, showing the lowest estimated 90% and 50% lethal concentrations (LC90 and LC50 ), followed by deltamethrin and thiamethoxam. Acetamiprid caused the highest levels of mortality and brood size reduction under extended laboratory conditions. Moreover, acetamiprid, thiamethoxam and lambda‐cyhalothrin caused the greatest mortality and, together with deltamethrin, strongly affected progeny occurrence inside infested galleries and beetle brood size. Among the bioinsecticides, pyrethrins significantly affected beetle survival under laboratory conditions, but not brood size in extended laboratory bioassays. Some of the tested insecticides had significant lethal and sublethal effects only when beetles were exposed to fresher residues, highlighting differences in toxicity persistence. CONCLUSION: This study provides first baseline toxicity data for synthetic insecticides and bioinsecticides with different modes of action and origin toward X. compactus, and the first evidence that several insecticides can cause multiple sublethal effects on this pest. These findings can help in building suitable integrated pest management packages against this pest. © 2023 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : This study provides first lethal and sublethal data for synthetic and bioinsecticides with different mechanisms of action and origin towards the invasive ambrosia beetle Xylosandrus compactus .